2022
DOI: 10.1002/jnr.25052
|View full text |Cite
|
Sign up to set email alerts
|

The role of the lateral septum in neuropsychiatric disease

Abstract: The lateral septum (LS) is a structure in the midline of the brain that is interconnected with areas associated with stress and feeding. This review highlights the role of the LS in anxiety, depression, and eating disorders and their comorbidity. There is a prevailing view that the LS is anxiolytic. This review finds that the LS is both anxiolytic and anxiogenic. Furthermore, the LS can promote and inhibit feeding. Given these shared roles, the LS represents a common site for the comorbidity of neuropsychiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 126 publications
0
5
0
Order By: Relevance
“…Our data demonstrate that dLS GLP-1R neuron inhibition potentiates food intake without affecting changes in anxiety-like behavior and locomotion. Previous studies have shown that the projections from the lateral septum to thalamic nuclei mediate stress and anxiety-like behavior, including both anxiolytic and anxiogenic effects [36][37][38][39][40][41]. We found that manipulations of dLS neurons or their projections to the LHA failed to affect anxiety-like behavior while still influencing food intake.…”
Section: Discussionmentioning
confidence: 52%
“…Our data demonstrate that dLS GLP-1R neuron inhibition potentiates food intake without affecting changes in anxiety-like behavior and locomotion. Previous studies have shown that the projections from the lateral septum to thalamic nuclei mediate stress and anxiety-like behavior, including both anxiolytic and anxiogenic effects [36][37][38][39][40][41]. We found that manipulations of dLS neurons or their projections to the LHA failed to affect anxiety-like behavior while still influencing food intake.…”
Section: Discussionmentioning
confidence: 52%
“…Our data demonstrate that dLS GLP−1R neuron inhibition potentiates food intake without affecting changes in anxiety-like behavior and locomotion. Previous studies have shown that the projections from the lateral septum to hypothalamic nuclei and the amygdala mediate stress and anxiety-like behavior, including both anxiolytic and anxiogenic effects [ [38] , [39] , [40] , [41] , [42] , [43] ]. We found that manipulations of dLS GLP−1R neurons or their projections to the LHA failed to affect anxiety-like behavior while still influencing food intake.…”
Section: Discussionmentioning
confidence: 99%
“…The LS is a structure that is interconnected with brain areas involved to cognition, motivation, autonomic regulation, stress and feeding ( Gray, 1977 ; Sheehan et al, 2004 ; Patel, 2022 ). It is part of a subcortical structure that delimits the midline of the brain called “septum” and is divided into two parts: the septum pellucidum and septum verum ( Andy and Stephan, 1968 ).…”
Section: The Lateral Septummentioning
confidence: 99%